Guidelines for implantation of a quality improvement training programme for health professionals in the ministry of health and social services in Namibia - Nangombe, Julia Paul; Amukugo, Hans Justus (International Journal of Health, 2016)
This paper is focuses on the description of the guidelines for implantation of a quality improvement training programme for health professionals. The formulation of the guidelines also borrowed the CDC (2001) steps and UNFPA phases of developing the guidelines for successful implementation of the training programme at the health care facilities in the MoHSS. The facilitator(s) and implementers of the training programme are advised to first understand the background and the development process of the training programme for successful implementation. These guidelines have been developed to assist quality manager(s) and facilitator(s) with the implementation of the quality improvement training programme for health professionals at the health care facilities (MoHSS).The guidelines enhance consistency in steps and methods to be followed during the implementation of the programme. The guidelines were derived from the conceptual framework that was developed during the exploratory and situation analysis of quality health care delivery at the health care facilities. Two prominent theories were adapted in developing these guidelines. Firstly, Deming’s PDSA model of quality improvement and secondly, Kolb’s experiential learning theory. These theories were used to understand the teaching and learning styles. The guidelines outlined the process, activities, and elements required to implement the such programme.